Peran Etika Profesi Akuntan dalam Mencegah dan Mendeteksi Fraud di Sektor Publik Indonesia - Husnul Hatimah, Melina, Tegar Firman Satriawan, Niken Meylianisapitri (Integrative Perspectives of Social and Science Journal, 2025)
This study aims to analyze the role of professional ethics of accountants in preventing and detecting fraud in the Indonesian public sector. Fraud in the public sector can cause major financial losses, reduce the efficiency of public budget use, and damage public trust in government institutions. Professional ethics of accountants, with the principles of integrity, objectivity, competence, confidentiality, and professional behavior, are expected to be the foundation in carrying out the duties and responsibilities of accountants to minimize the risk of fraud. This study uses a qualitative approach with a case study method in 5 public sector organizations and in - depth interviews with 15 accountants, internal auditors, external auditors, and other related parties to understand the perceptions and practices of accountants related to professional ethics in the context of fraud prevention and detection. The results of the study indicate that the understanding and application of professional ethics by accountants have a significant influence on the effectiveness of fraud prevention and detection, but its implementation faces challenges such as conflicts of interest and lack of ethical awareness.